Treatment effectiveness in a rare oncology indication: Lessons from an external control cohort study - Dina Oksen; Patricia Prince; Emmanuelle Boutmy; Elizabeth M. Garry; Barbara Ellers‐Lenz; Adina Estrin; Andreas Johne; Patrice Verpillat; Nicolle M. Gatto (Wiley, 2022)
Abstract Real‐world data (RWD) reflecting patient treatment in routine clinical practice can be used to develop external control groups for single‐arm trials. External controls can provide valuable benchmark results on potential comparator drug effectiveness, particularly in rare indications when randomized controlled trials are either infeasible or unethical. This paper describes lessons learned from a descriptive real‐world external control cohort study conducted to provide benchmark data for a single‐arm clinical trial in a rare oncology biomarker driven disease. Conducting external control cohort studies to evaluate treatment effectiveness in rare indications likely will present data and analysis challenges as seen in the example study. However, there are mitigating measures that can be applied in the study design, identification of RWD sources, and data analysis. The lessons learned and reported here with a proposal of an external control study framework can provide guidance for future research in this area, and may be applicable as well in other rare indications. Taking these learnings into consideration, the use of real‐world external controls to contextualize treatment effectiveness in rare indications is a valuable approach and warrants further application in the future.